Exploring the Anti-diabetic Properties of Edible Mushrooms: A Comprehensive Review - Reddy, H.Rama Subba; Kumar, M.Vijaya; Lakshmaiah, G.; Babu, K.Harish; Aruna, C.; Kumar, D. Veera Nagendra; Kiran, V.Uday (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Mushrooms, part of the “Fungi” family is well-known for their medical benefits and accessibility globally. Diabetes has become more commonplace worldwide in recent times, which has made the search for alternate treatment approaches necessary. Because of their possible anti-diabetic effects, edible mushrooms—a natural source of bioactive compounds—have drawn interest. This research assesses the possible anti-diabetic benefits of edible mushrooms, concentrating on their bioactive constituents and mechanisms that modulate insulin sensitivity and glucose metabolism, and emphasises their potential significance in diabetes prevention. The review concludes that EM can predict insulin resistance through active chemicals like polysaccharides and vitamin D, as well as preventative activities like β-glucosidase and β-amylase. The therapeutic benefits of many mushroom types have not been thoroughly researched, and the mechanism remains unclear. More study on edible medicinal mushrooms is needed to fully utilise their therapeutic promise in preventing noncommunicable diseases.